Consistent individual differences in haemolymph density reflect risk propensity in a marine invertebrate. Issue 6 (June 2015) - Fürtbauer, Ines
Abstract : While the literature on consistent individual differences in correlated suites of physiological and behavioural traits is steadily growing for vertebrates, invertebrates have received less attention. The few studies that do exist have measured temporary physiological states (or responses), rather than consistent individual physiological traits. Here, I explore the consistency of individual differences in physiology and behaviour of n =53 shore crabs ( Carcinus maenas ) by repeatedly measuring haemolymph density (HD) and the crabs' responses to a novel environment. In crustaceans, HD is directly proportional to protein concentrations, and thus indicative of physiological condition. HD was highly repeatable, and crabs showed consistent individual differences in their behavioural responses to a novel environment, thus indicating individual consistency in both physiology and behaviour. Furthermore, HD was significantly correlated with the crabs' risk propensity, i.e. individuals with higher HD spent more time near shelter. Overall, this provides the first evidence for consistency in an endogenous physiological trait in an invertebrate. The link between consistent physiology and behaviour, i.e. coping styles, analogous to those found in vertebrates, suggests metabolic and/or immunological correlates of personality which offer great potential for future studies.